Covid-19 pandemic- A global concern - Chowdhury, Md. Zaforullah (Update Dental College Journal, 2022)
The world faces a severe and acute public health emergency due to the corona virus pandemic COVID-19. On 31st December 2019, a new coronavirus causing pneumonia emerged in Wuhan, China, which was confirmed by the World Health Organization (WHO)'. After the identification of the first case, till the 1st week of March 2022 448,175,126 confirmed cases and 6,027,357 deaths reported by WHO globally. As the virus is highly contagious and due to its rapidly spreading in nature, on March 11, 2020, WHO declared the disease as a pandemic. In Bangladesh, the first case was confirmed on March 8, 2020. Initially, it was named 2019-nCoV but later officially it was named severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) by the Coronavirus Study Group of the International Committee on Taxonomy of Viruses (ICTV) and the disease caused by this virus was named COVID-19 by the WHO. Complete genome sequencing confirms the virus belongs to the beta coronavirus genus. Delta variant spread in the community having more pathogenic and responsible for a large no of death. Subsequently, new variant B.1.1.529 named as omicron variant came into the community which spread more but was less pathogenic. Although now treatment and vaccine are available, there are many infected patients with no symptoms and slight illness, who spread the virus into the society insidiously. In addition to effective personal protection measures, the vaccination can prevent the disease and limit the spread of infection. Update Dent. Coll. j: 2022; 12(1): 1-2